LGU CHAIRMAN, VICE-CHANCELLOR EXTEND CONGRATULATIONS TO 5 TRSM RECIPIENTS - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 31 October 2015 – The Chairman of Universiti Sains Malaysia (USM) Board of Governors, Tan Sri Datuk Dr. Zulkefli A. Hassan and the ViceChancellor, Professor Dato' Dr. Omar Osman congratulated the five USM scientists who were acknowledged as the Top Research Scientists Malaysia (TRSM) by the Academy of Sciences Malaysia (ASM) today.